Non-medical influences on medical decision-making - McKinlay, John B.; Potter, Deborah A.; Feldman, Henry A. (Social science & medicine (1982), 1996)
Background. The influence of non-medical factors on physicians' decision-making has been documented in many observational studies, but rarely in an experimental setting capable of demonstrating cause and effect. We conducted a controlled factorial experiment to assess the influence of non-medical factors on the diagnostic and treatment decisions made by practitioners of internal medicine in two common medical situations. Methods. One hundred and ninety-two white male internists individually viewed professionally produced video scenarios in which the actor-patient, presenting with either chest pain or dyspnea, possessed various balanced combinations of sex, race, age, socioeconomic status, and health insurance coverage. Physician subjects were randomly drawn from lists of internists in private practice, hospital-based practice, and HMO's, at two levels of experience. Results. The most frequent diagnoses for both chest pain and dyspnea were psychogenic origin and cardiac problems. Smoking cessation was the most frequent treatment recommendation for both conditions. Younger patients (all other factors being the same) were significantly more likely to receive the psychogenic diagnosis. Older patients were more likely to receive the cardiac diagnosis for chest pain, particularly if they were insured. HMO-based physicians were more likely to recommend a follow-up visit for chest pain. Several interactions of patient and physician factors were significant in addition to the main effects. Conclusions. The variability in decision-making evidenced by physicians in this experiment was not entirely accounted for by strictly rational Bayesian inference (the common prescriptive model for medical decision-making), in-as-much as non-medical factors significantly affected the decisions that they made. There is a need to supplement idealized medical schemata with considerations of social behavior in any comprehensive theory of medical decision-making.